A Fixed Point Approach to the Stability of a Cauchy-Jensen Functional Equation - Jae-Hyeong Bae; Won-Gil Park (Abstract and Applied Analysis)
We find out the general solution of a generalized Cauchy-Jensen functional equation and prove its stability. In fact, we investigate the existence of a Cauchy-Jensen mapping related to the generalized Cauchy-Jensen functional equation and prove its uniqueness. In the last section of this paper, we treat a fixed point approach to the stability of the Cauchy-Jensen functional equation.